Precisão de moldagens para implantes inclinados em maxila utilizando diferentes métodos de união de transfrentes e dois tipos de guias multifuncionais - Araújo, Raphael Ferreira de Souza Bezerra [UNESP] (2015)
This study analyze in vitro the accuracy of different union transfers methods in impressiom using multifunctional guides for prosthetic rehabilitation in a toothless jaw with external hexagon implants installed. For the impression techniques with two types of multifunctional guide (palate coverage and open palate) it was compared different methods of union of the square transfers: metal splinted transfers, acrylic resin splinted transfers and without splinted transfers. A metal structure fabricated on the master model with passive fit was screwed in the models obtained, on A analogue while measurements were made 3 times on analogs C and D and when screwed into analog D measurements were made 3 times in analogues A and B, by a image analysis software (Leica QWin) that received the images from a video camera attached to a Leica magnifier (100X). After verification of distribution and homoscedasticity data, statistical methods (α = 0.05) were used to assess the influence of the independent variables. In general, larger models generated fringe displacement in relation to the master model, irrespective of splint techniques. But only exist statistical differences when compared the impression technique OM = 203,04µm (multifunctional guide with open palate and transfers splinted with metal and acrylic resin) with impression technique PR = 151,61µm (multifunctional guide with coverage palate and transfers splinted with resin acrylic) and the master model (MM = 142,78µm). Considering the limitations of this study may suggest that the use of OM molding technique generates less accurate models.